KONSEP MAKANAN HALAL DAN THOYYIB DALAM TRADISI MASYARAKAT MELAYU RIAU - Edison, Edison; Lestari, Rini (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2020)
Besides receiving education and teaching about the virtues of halal food according to the Melayu tradition, Riau community should also get an understanding of the virtues of halal food based on the Islamic law. This study aims to analyze the concept of the Riau Malay community in maintaining halal food, and what is the manners eat traditions of Melayu society closely related to eating etiquette in Islam. This research was a field study that collects data based on interviews, observation and documentation. The results showed that the food of the Melayu community has met the elements of halal and thoyyib as stipulated in culinary fiqh in Islamic law. The motive of the Melayu community to eat with halal and thoyyib criteria’s food is more due to habits and traditions that have been taught from generation to generation through the advice and teachings of the elders. This study also revealed that the type of food that is legalized is more than the type of food that is forbidden. Although the Malay community has been taught about the concept of halal food and thoyyib, but the teaching did not contain systematic content and had not yet reached a comprehensive level of understanding.